Liquidity risk and liquidity timing in the cross-section of Indian equity mutual fund returns - Kumar, Suresh; Ali, Hyder (Economics and Business Review, 2026)
This study examines how aggregate market liquidity influences the cross-section of Indian equity mutual fund returns through two mechanisms: (1) funds’ long-run exposure to liquidity risk, and (2) managers’ time-varying liquidity timing. Using a comprehensive sample from 2007–2024, we estimate rolling liquidity betas, form portfolios sorted by liquidity exposure, and compute a high-minus-low liquidity‑beta return spread. The liquidity premium is positive and economically meaningful in tranquil and recovery regimes, but weakens or vanishes during systemic stress, consistent with state-dependent liquidity pricing. Adding a traded equity-liquidity factor to standard benchmarks explains a meaningful portion of the spread, while an independently constructed timing factor captures an additional 55%–64%, highlighting the importance of conditional beta management. Timing effects are concentrated among high-liquidity-beta funds, smoothing returns in normal markets but offering limited protection in crises. Findings are robust to alternative benchmarks, flow-adjusted timing specifications, and post-COVID subperiod definitions.